Pengaruh Pemberian Pupuk Hayati dan Penambahan Limbah Baglog Jamur Terhadap Pertumbuhan Dan Hasil Tanaman Buncis (Phaseolus Vulgaris L) - Mirinda Retno Wulandari; Sri Hartatik (Berkala Ilmiah Pertanian, 2022)
Beans ( Phaseolus vulgaris L ) is shrubs that are included in annual crops. Bean plants have a high nutritions. According to the Central Bereau of Statistic (2021), the production of beans in Indonesian has fluctuated in 2018 – 2021. Fluctuating bean production has an impact on consument needs. One of the obstacles to increasing bean production is the large use of inorganic fertilizers which can have negative impact. Efforts to increase the productivity of beans are one of them using biological fertilizers combined with mushroom baglog waste. The purpose of this study wasto determine the effect of the dose of biological fertilizer and the addition of mushroom baglog waste on the growth and yield of beans.The study used a factorial completely randomized design (CRD) with two factors. The first factor was the dose of biological fertilizer with treatment H0 : control; H1 : 15 ml/L water; H2 : 30 ml/L water. The second factor is the addition of baglogw aste with L0 : without mushroom baglog waste; L1 : 50 gram/polybag; L2 : 100 gram/polybag. The results showed 1) The interaction of biological fertilizers and baglog waste was only significantly different on the root lenght variable. 2) The best treatment was 30 ml/l water of biological fertilizers. 3) The best treatment was 100 grams of baglog. Keywords: Beans, Biofertilizer, Mushroom baglog waste, Dose